Práticas insurgentes: possíveis encontros entre psicologia e arte em conexão com territórios escolares - Gonçalves, Lara Thayse de Lima (2023)
The Artes Insurgentes: Coletivizando Resistências project was created by graduate and postgraduate Psychology students in 2021, aiming to act with youth collectives that use the art practice as way to be politically active. The project forecasts, through artistic-cultural workshops, the problematization of the day-to-day life of young students from public high schools in the Grande Bom Jardim area, located in the suburb of Fortaleza/CE organizing, with youth collectives of that region, an articulation between Psychology-Art-School. If historically the approximation between Psychology and Schools was based on using the psychology knowledge for students’ adjustment, under an adaptationist rationality, we question if, by establishing a relationship with Art, the project in question could contribute to an repositioning of the psychology practice, aiming to create a different field of sayability concerning the suburb’s youth. Therefore, this investigation’s main goal is to analyse the articulation between Psychology, Art and School through the discursive constructions of graduate and postgraduate Psychology students that are apart of Artes Insurgentes: Coletivizando Resistências about their experiences on said project. The specific goals: problematize the relationship between the participants of Artes Insurgentes: Coletivizando Resistências and the schools; discuss the artistic processes as a possible articulation deterritorialize the psychology practices with public high schools and its youths; and, at last, discuss “intervision” as a methodological device of the research process. Thereunto, this research articulates academic works that discuss the relationship between Psychology, Art and Schools, as well as works about the possible interactions between the three fields, with Foucault, Deleuze, Guattari, Zanella, Zanetti, among others’ writings. The methodological construction of this investigation is sustained by Intervention Research, the comprehends the collective production of the research process in a critical and implicated form. The research devices are: “intervision” meetings that lasted two hours every other week with 8 graduate students and 4 postgraduate students, all part of the project, as well as field journals about the projects’ activities and art work created during “intervision” with said members. The analysis were made through an inspiration on Foucault’s based Discourse Analysis. The data produced indicate that the articulation between Art and Psychology have been producing strategies for the reinvention of what could be a practice in psychology with young students from GBJ, stimulating the decolonization as an ethical posture in said project, aiming to claim social justice and abandoning individualizing ways of acting in psychology in the daily construction of Artes Insurgentes. That way, the research process made it possible to discuss and produce as a collective, recreating the relationship between the three fields in question for the groupthat participates in the project, strengthening the group’s implication with what happens when in the action field of the project.